Galloping Gertie : the true story of the Tacoma Narrows Bridge collapse - Abler, Amanda (Little Bigfoot : Sasquatch Books, 2021)
Dale, a young boy living in Tacoma, Washington in the 1940s, describes the opening of the Tacoma Narrows Bridge, and his memories of watching it collapse on his birthday a few months later. Back matter includes information about why the bridge collapsed, how the design was altered, how the catastrophe helped engineers build better bridges, bridges with similar issues, a diagram of a suspension bride with information about how they work, links to videos, and a glossary.